Influência da pressão arterial sistêmica na disfunção erétil em pacientes com doença arterial periférica - Spessoto, Luís Cesar Fava (2010)
One of the symptoms of peripheral artery disease (PAD) is erectile dysfunction (ED) which is characterized by a man s persistent inability to obtain and maintain a sufficient erection for satisfactory sexual intercourse. An elevation in the systemic arterial blood pressure is a common risk factor of both ED and PAD. Objective: The aim of this study was to study the influence of systemic arterial blood pressure on ED in patients with PAD. Patients and method: Fifty-two patients with ED with and without cardiovascular risk factors and with ages ranging from 42 to 78 years old (56.63 ± 10.34 years) were studied from January to June 2009. The ED was classified as mild, moderate and severe utilizing the International Index of Erectile Function. A physical examination was carried including measurement of the ankle-arm index (AAI), determined as the ratio between the highest systolic artery pressure (SAP) comparing ankles and the highest SAP between the brachial arteries. Statistical analysis was achieved by binary logistic regression, Pearson Chi-squared test, the log-likelihood ratio Chi-squared test for independent samples and the Kruskal-Wallis test. The level of significance was set for an alpha error of 5% (p-value < 0.05). Results: Of the studied patients, 11/52 (21.2%) had mild (Grade 1), 24 (46.1%) had moderate (Grade 2) and 17 had severe ED (Grade 3). The SAP in the brachial and anterior tibial arteries varied xi from 110 to 190 mmHg and from 90 to 180 mmHg, respectively. In respect to the AAI, 28 (53.8%) of the patients presented normal values or above 0.9 and 24 (46.2%) presented values of less than 0.9 thereby identifying PAD. Significant differences were identified on comparing the median degree of dysfunction of patients in different phases of PAD (p = 0.001) and between Grade 1 and Grade 3 (p = 0.0003) using the Kruskal-Wallis test with Bonferroni correction for multiple comparisons. Binary logistic regression showed that normotensive individuals in the initial phase of PAD with AAI between 0.8 and 0.9 presented with more severe ED when compared to hypertensive patients. Conclusions: An elevated systemic arterial pressure may have a protective effect against erectile dysfunction in the initial phases of peripheral arterial disease.